2016
DOI: 10.1080/10410236.2015.1089456
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Self-Efficacy, Response Efficacy, and Reactance on Responses to Cigarette Health Warnings: A Longitudinal Study of Adult Smokers in Australia and Canada

Abstract: Guided by the extended parallel process model (EPPM) and reactance theory, this study examined the relationship between efficacy beliefs, reactance, and adult smokers’ responses to pictorial health warning labels (HWL) on cigarette packaging, including whether efficacy beliefs or reactance modify the relationship between HWL responses and subsequent smoking cessation behavior. Four waves of data were analyzed from prospective cohorts of smokers in Australia and Canada (n = 7,120 observations) over a period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
75
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 61 publications
12
75
2
4
Order By: Relevance
“…They found that large, graphic warnings work indirectly through several underlying factors: they encouraged smokers to think about the risks of smoking, which elicited emotional responses such as worry about health risks, which in turn increased intentions to quit and encouraged subsequent quitting behavior. In addition, contrary to the idea that extreme fear arousal results in message rejection (Kessels, Ruiter, Wouters, & Jansma, 2014; Kessels, Ruiter, & Jansma, 2010), avoidance behavior was associated with increased frequency of thinking about health risks (Yong et al 2014) and subsequent cessation attempts (Thrasher et al 2016). Together, these findings support the use of graphic, fear-arousing tobacco health warnings.…”
Section: Discussionmentioning
confidence: 69%
“…They found that large, graphic warnings work indirectly through several underlying factors: they encouraged smokers to think about the risks of smoking, which elicited emotional responses such as worry about health risks, which in turn increased intentions to quit and encouraged subsequent quitting behavior. In addition, contrary to the idea that extreme fear arousal results in message rejection (Kessels, Ruiter, Wouters, & Jansma, 2014; Kessels, Ruiter, & Jansma, 2010), avoidance behavior was associated with increased frequency of thinking about health risks (Yong et al 2014) and subsequent cessation attempts (Thrasher et al 2016). Together, these findings support the use of graphic, fear-arousing tobacco health warnings.…”
Section: Discussionmentioning
confidence: 69%
“…En dicho modelo se han establecido relaciones directas e indirectas con los aspectos de autoeficacia en el cuidado de la salud evaluados mediante el cuestionario EACASF. Dada la importancia de la autoeficacia en la adquisición de hábitos saludables (Luszczynskay & Schwarzer, 2005) y su capacidad predictiva en la realización de conductas de autocuidado de la salud (Thrasher, et al, 2016), se ha considerado fundamental asegurar que el instrumento de evaluación es válido y fiable en la muestra evaluada. En este sentido, los análisis factoriales confirmatorios para el cuestionario de autoeficacia en el cuidado de la alimentación y la salud física (EACASF) muestran que una estructura pentafactorial es viable y adecuada.…”
Section: Discussionunclassified
“…Una de las variables estudiadas ha sido la autoeficacia, concepto ampliamente descrito desde la teoría de Bandura, donde se enfatiza que la autoeficacia es un aspecto clave, entre otros, para adquirir o mejorar, conductas saludables (Luszczynska & Schwarzer, 2005). De esta forma, las creencias sobre la capacidad de cuidar la propia salud pueden predecir la realización de dicho autocuidado (Thrasher, et al, 2016). En esta línea, algunos autores han señalado a la autoeficacia como una variable predictora en la intención de ingerir alimentos bajos en calorías, frutas y verduras (Povey, Conner, Sparks, James, & Shepherd, 2000) mencionándola como uno de los elementos para fomentar el estilo de vida saludable (González-Cantero, et al, 2017), reducir el peso en personas adultas con sobrepeso (Annesi & Tennant, 2014) y mantenerlo en personas con normopeso (Teixeira, et al, 2010).…”
Section: Introductionunclassified
“…In particular, the extended parallel process model (EPPM; Witte, 1992) proposes that in order to respond to health risks adaptively, people will need to perceive themselves at risk (risk perception) and have confidence in their ability to mitigate that risk (self-efficacy). This model has previously been applied to smoking behaviour, particularly in the context of health risk communication (e.g., Thrasher et al, 2016). This model has previously been applied to smoking behaviour, particularly in the context of health risk communication (e.g., Thrasher et al, 2016).…”
Section: Statement Of Contributionmentioning
confidence: 99%
“…The model proposes that intentions to change are unlikely to develop unless one considers oneself susceptible to a threat of sufficient severity and simultaneously capable of averting it. This model has previously been applied to smoking behaviour, particularly in the context of health risk communication (e.g., Thrasher et al, 2016). However, like most theories of health behaviour, the EPPM is silent on the role of time in the conceptualization of these constructs (cf., Scholz, 2019).…”
Section: Statement Of Contributionmentioning
confidence: 99%